Rationalize: `1/(sqrt x + sqrt y)`

### 1 Answer | Add Yours

The expression `1/(sqrt x + sqrt y)` has to be rationalized.

`1/(sqrt x + sqrt y)`

=> `(sqrt x - sqrt y)/((sqrt x + sqrt y)(sqrt x - sqrt y))`

=> `(sqrt x - sqrt y)/((sqrt x)^2 - (sqrt y)^2)`

=> `(sqrt x - sqrt y)/(x - y)`

**The rationalized form of `1/(sqrt x + sqrt y) = (sqrt x - sqrt y)/(x - y)` **

=> (sqrt x - sqrt y)/((sqrt x + sqrt y)(sqrt x - sqrt y))

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes